Evaluation of Anti-Thyroglobulin, Anti-Thyroid Peroxidase Autoantibodies and Thyroid Stimulating Hormone in Autoimmune Thyroiditis Patients - Sahib, Noor Al-Huda Fadhil; Mohammed, Kareem Ghali (Medical Science Journal for Advance Research, 2024)
Background: Thyroiditis is a broad term used to describe a range of clinical illnesses characterized by inflammation and damage to cells in the thyroid gland. These abnormalities may arise from several causes, such as radiation exposure, microbial infection, or association with autoimmune thyroid illnesses, such as Hashimoto’s thyroiditis (HT) and Graves' disease (GD). Aim of the study: This cross-sectional study aimed to evaluation of anti-thyroid antibodies (anti-thyroglobulin and anti-thyroid peroxidase) and thyroid stimulating hormone (TSH) thyroiditis patients. The study involved a 100 patients afflicted with Thyroid dysfunction can be detected through a physical examination and certain tests. Method and results: The concentrations of thyroid hormones (thyroxine (T4) and 3,5,3′-triiodothyronine (T3)) and TSH were measured to determine the patients who have hypothyroidism or have hyperthyroidism. Then the patients determined which of them had autoimmune thyroid disease by the detection of thyroid autoantibodies (anti-thyroglobulin (anti-TG) and anti-thyroid peroxidase (anti-TPO) antibodies). The tests were separated into two groups (Graves and Hashimoto). Mean levels of serum TSH are 19.79 ± 2.62 and 0.39±0.11, in patients with HT and patients with GD respectively; The levels of HT patients are much greater compared to GD patients, with a very significant difference (P < 0.001). The present results show the mean level of anti-TPO Abs in patients with HT is non-significant difference than the mean of anti-TPO Abs level in patients with GD, 745.74 ± 82.02 versus 841.07 ± 92.01 respectively, (P= 0.440). Also, the mean level of anti-TG Abs is higher in patients with HT in comparison with patients with GD and the difference is non-significant, (P= 0.929).The mean age of patients diagnosed with HT is 41.49 ± 10.57 years, with a range of 15 to 65 years. On the other hand, the mean age of patients diagnosed with GD is 42.35 ± 11.64 years, with a range of 21 to 70 years. Indeed, there is no significant difference in mean age between patients groups (P= 0.698). Sex, in overall, 19 (19.0%) males and 81 (81.0%) females are included. patients with HT included 13 (23.6%) cases are males and 42 (76.4%) cases are females, while patients with GD, 6 (13.3%) cases are males and 39 (86.7%) cases are females, there is no significant variation in the frequency distribution of both groups of patients based on sex (P = 0.191). BMI, the present results show the mean of BMI is higher in patients with HT (30.01 ± 7.08) in comparison that of patients with GD (27.24±4.83) (P=0.034). Conclusion: The serum TSH, anti-TPO and anti-TG Abs levels can serve as an important predictive biomarker in AITDs diagnosis.